Higher blood loss and transfusion requirement in surface arthroplasty versus conventional total hip replacement - Regis, Dario; Sandri, Andrea; Sambugaro, Elena; Franchini, Massimo; Vecchini, Eugenio; Samaila, Elena; Magnan, Bruno (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Surface replacement arthroplasty (SRA) is an alternative to stemmed total hip arthroplasty (THA) providing a femoral bone preserving procedure. Because of the wider surgical dissection, an increased blood loss could be expected. This retrospective study evaluates the transfusion requirement in two homogeneous groups of patients who underwent primary hip replacement electively. Methods: Perioperative haematological data of 42 hip resurfacing procedures and 41 conventional cementless THAs were compared. The pre- and post-operative haemoglobin (Hb) levels and the amount of blood transfusions were registered. The median values were compared with use of the non-parametric Wilcoxon signedrank test. Results: In the SRA group, a significantly increased (p